A Comprehensive Study of Mana in Shavasana - Saini, Kratika; Kumari, Priyanka; Thakur, Balaji; Singh, Bhanu Pratap (International Research Journal of Ayurveda & Yoga, 2022)
Increase incidence of Manasika Vikara or mental illness is the main concern in today’s world. Manasika dosha generally vitiates the mind and causes different psychological conditions. In Bhagvat Gita lord Krishna says that, our Aatma is our real friend but positive thinking and control over mind is very important otherwise it becomes our enemy and at that time mental disorders occur. There are so many treatments described in ayurvedic and modern practises. As prevention is better than cure its better to practise yoga to reduce stress. several studies on result of standard observe of yogasana have discovered physical and mental welfare. In today’s world, everybody feels stressed from time to time, Stress may be a feeling of being beneath abnormal pressure. This pressure will come back from totally different aspects of your daily life. In currently stress is taken into account a significant causative issue for several diseases. In several analysis it’s been found that Stress caused thanks to varied factors that have an effect on vascular system. Several studies have shown that active of Shavasana decreases the guts rate, improves the compliance of the blood vessels, regulates regular recurrence, and will increase the stroke volume. This article is tried to focus on, how Shavasana affect our mind form classical and modern point of view.